Evaluating online teaching implementing best practices - Tobin, Thomas J.; Mandernach, B. Jean; Taylor, Ann H. (San Francisco, CA Jossey-Bass, 2015)
Evaluating Online Teaching is the first comprehensive book to outline strategies for effectively measuring the quality of online teaching, providing the tools and guidance that faculty members and administrators need. The authors address challenges that colleges and universities face in creating effective online teacher evaluations, including organizational structure, institutional governance, faculty and administrator attitudes, and possible budget constraints. Through the integration of case studies and theory, the text provides practical solutions geared to address challenges and foster effective, efficient evaluations of online teaching. Readers gain access to rubrics, forms, and worksheets that they can customize to fit the needs of their unique institutions. Evaluation methods designed for face-to-face classrooms, from student surveys to administrative observations, are often applied to the online teaching environment, leaving reviewers and instructors with an ill-fitted and incomplete analysis. Evaluating Online Teaching shows how strategies for evaluating online teaching differ from those used in traditional classrooms and vary as a function of the nature, purpose, and focus of the evaluation. This book guides faculty members and administrators in crafting an evaluation process specifically suited to online teaching and learning, for more accurate feedback and better results. Readers will: Learn how to evaluate online teaching performance; Examine best practices for student ratings of online teaching; Discover methods and tools for gathering informal feedback; and Understand the online teaching evaluation life cycle. The book concludes with an examination of strategies for fostering change across campus, as well as structures for creating a climate of assessment that includes online teaching as a component. Evaluating Online Teaching helps institutions rethink the evaluation process for online teaching, with the end goal of improving teaching and learning, student success, and institutional results.--Provided by publisher.
Planning: Challenges in evaluation of online teaching ; Context for evaluating online teaching ; Establishing a foundation for evaluating online teaching -- Formative evaluation: Conducting formative reviews to enhance online teaching -- Summative evaluation: Student ratings of online teaching ; Administrative evaluation of online teaching ; Administrative review tools ; Integrating data analytics in the evaluation of online teaching -- Sustaining a culture of evaluation: From tools to processes ; Implementing the evaluation process ; The online-teaching evaluation life cycle ; Next steps..
Includes bibliographical references (pages 261-268) and index.
Keywords: ducation, Higher -- Computer-assisted instruction; Web-based instruction -- Evaluation; Distance education -- Evaluation; Internet in education; World Wide Web -- Study and teaching (Higher).; Teachers -- Training of; Teacher effectiveness